Confessions of Contemporary Western and Arab Critics of the Deconstructive Criticism Crisis - RAJAH , Samia (Milev Journal of Research and Studies, 2020)
The reader stands in this critical study at the most important theoretical and procedural problems that were riddled with the strategy of deconstructive criticism, and this is illustrated by shedding light on the total condemnations and oppositions to the dismantling, and the focus has been on distinguished critical flags, including what contributed to the establishment of this critical strategy The new; I mean the dismantling strategy, and among those critical Western flags we mention: Jacques Derrida, Jose Maria Bothwellwa Evancus, Leach, Howard Flearn, John Ellis, Leonard Jackson, Paul Deman and J. Lubran, Vedence Dunoye, and Maury Krieger. Among the contemporary Arab critics denouncing deconstructive criticism, we mention: Edward Said, Shuja Muslim, Bassam Qattoos, Abdel Aziz Ibn Arafa, Abdel Aziz Hamouda and Abdel Hamid Ibrahim. I would like to point out in this context that this study is not merely a tedious presentation or narration of these criticisms. We have worked on explaining it, describing it, and commenting on it critically, through which we aimed to present a future picture of the world of deconstructive criticism by presenting some new critical suggestions that would Restoration of the think tank, with its theoretical spurs and promising procedural perspectives.